INFLUENCE OF POMEGRANATE JUICE ON THE CYP3A4-MEDIATED METABOLISM AND P-GLYCOPROTEIN MEDIATED TRANSPORT OF SAQUINAVIR IN VIVO AND EX VIVO MODELS - Vemulapalli, Sridhar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Cytochrome P450 3A4 (CYP3A4) and P-glycoprotein (P-gp) play an important role in the first pass metabolism thereby limits the oral bioavailability of many clinically important and frequently prescribed drugs. The absolute oral bioavailability of saquinavir is very low (i. e. 4%) due to its extensive first pass metabolism by the major metabolizing isozyme CYP3A4 and it is also a substrate of P-gp. Pomegranate juice (PGJ) was known to be a modulator of CYP3A4 and P-gp. Therefore, the aim of this study was to evaluate the influence of PGJ on the pharmacokinetics (PK) of saquinavir in wistar rats and on the P-gp mediated intestinal transport of saquinavir in everted gut sacs ex vivo. Â Rats were treated orally with saquinavir (100 mg/kg) alone and in combination with PGJ (0.5, 1.0 and 2.0 mL/200g, body weight) for 15 consecutive days. Blood samples were collected on 1st day in single dose pharmacokinetic study (SDS) and on 15th day in multiple dose pharmacokinetic study (MDS). The peak plasma concentration (Cmax)and area under the plasma concentration-time curve (AUC0-24) of saquinavir was increased with PGJ in SDS (p<0.001) may be due to inhibition of CYP3A4 and P-gp. But interestingly, the Cmax and AUC0-24 of saquinavir was decreased significantly with PGJ in MDS. This is may be due to induction of CYP3A4. The transport of saquinavir was increased in presence of PGJ and known P-gp inhibitors (Verapamil, Ketoconazole and Quinindine) across the rat everted gut sacs ex vivo. The present study results suggested that PGJ has both effects (inhibition, in SDS and induction, in MDS) on CYP3A4-mediated saquinavir metabolism in vivo and inhibitory effect on the P-gp mediated intestinal transport of saquinavir ex vivo. Further studies are needed to confirm this interaction at cellular level using cell lines and in humans.